2017
DOI: 10.1021/acsmedchemlett.7b00317
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of VU6005649, a CNS Penetrant mGlu7/8 Receptor PAM Derived from a Series of Pyrazolo[1,5-a]pyrimidines

Abstract: Herein, we report the structure-activity relationships within a series of mGlu PAMs based on a pyrazolo[1,5-]pyrimidine core with excellent CNS penetration (s > 1 and s> 1). Analogues in this series proved to display a range of Group III mGlu receptor selectivity, but VU6005649 emerged as the first dual mGlu PAM, filling a void in the Group III mGlu receptor PAM toolbox and demonstrating efficacy in a mouse contextual fear conditioning model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…12,13 Recent efforts to develop a first-in-class mGlu 7 PAM to further validate the Rett connection resulted in an mGlu 7 -preferring PAM 1, VU6005649, that demonstrated pro-cognitive effects on associative learning in wild type mice. 14 There have been several mGlu 7 NAM tools reported in the literature ( Figure 1), 15−17 and the therapeutic potential of mGlu 7 has been reviewed. 18 In 2007, Tsukuba researchers reported on the first mGlu 7 NAMs 2 (MDIP) and 3 (MMPIP); 15 however, subsequent work with 2 and 3 demonstrated contextdependent pharmacology in cells and a lack of activity in electrophysiological studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Recent efforts to develop a first-in-class mGlu 7 PAM to further validate the Rett connection resulted in an mGlu 7 -preferring PAM 1, VU6005649, that demonstrated pro-cognitive effects on associative learning in wild type mice. 14 There have been several mGlu 7 NAM tools reported in the literature ( Figure 1), 15−17 and the therapeutic potential of mGlu 7 has been reviewed. 18 In 2007, Tsukuba researchers reported on the first mGlu 7 NAMs 2 (MDIP) and 3 (MMPIP); 15 however, subsequent work with 2 and 3 demonstrated contextdependent pharmacology in cells and a lack of activity in electrophysiological studies.…”
mentioning
confidence: 99%
“…21 The steep (all active analogues possessed IC 50 s in the ∼700 nM range) and flat (minor structural changes led to loss of mGlu 7 NAM activity) SAR profile of analogs 11 left five analogues (11a−e) for DMPK profiling to assess potential as in vivo tools. 14,20,21 As in vitro potency and CNS penetration were generally conserved and favorable for 11a−e, in vitro DMPK profiles (Table 2) were employed to prioritize advanced characterization toward a tool compound. In terms of cLogP (2.86), molecular weight (408), and fraction unbound in both mouse ( f u = 0.178) and rat ( f u = 0.244) plasma and rat brain ( f u = 0.038), 11a (VU6010608) was superior among the new analogues 11.…”
mentioning
confidence: 99%
“…In addition to its activity on mGlu 8 , VU6005649 displays off-target effects at the neurokinin-1 receptor (NK1). It is believed that these effects on NK1 may mediate sedative effects of this compound, which are observed in both wild-type and mGlu 7 knockout animals ( Abe et al, 2017 ). Because many of these tool compounds are not selective, they have been used concomitantly with other molecules, such as the mGlu 4/8 PAM ADX88178 ( 7 ) or mGlu 7 NAM ADX71743 ( 8 ), to confirm mGlu 7 -mediated effects ( Le Poul et al, 2012 ; Kalinichev et al, 2013 , 2014 ; Gogliotti et al, 2017 ).…”
Section: Current Mglu 7 Tool Compoundsmentioning
confidence: 99%
“…However, Ahnaou et al (2016) demonstrated that AMN082 produced similar sleep-wake and hypothermia phenotypes in Grm7 -/- and wild-type mice, suggesting that there may be off-target effects elicited by the compound. Additionally, administration of VU6005649, an mGlu 7/8 PAM, to wild-type mice, increases freezing in contextual fear conditioning ( Abe et al, 2017 ).…”
Section: Cognitionmentioning
confidence: 99%
“…6). 40 Compound 15 was selected after an HTS as an interesting hit with selectivity for mGlu7 versus mGlu4 and mGlu8 receptors and excellent CNS penetration in rats (plasma/brain K p = 1.4, K p,uu = 1.1). Furthermore, the chemical structure of 15 was amenable for an efficient parallel SAR exploration of the four substituents around the pyrazolopyrimidine central core.…”
Section: Positive Allosteric Modulators (Pams)mentioning
confidence: 99%